Cardiac Tamponade Secondary to a Giant Pleuropericardial Cyst in a Child: A Surgical Case Report from Sub-Saharan Africa - Bori Bata, Abdel Kémal; Imorou-Souaibou, Yacoubou; Ibrahim, Ahmad; Nékoua, Désiré; Adoco, Joseph; Sonou, Arnaud (European Journal of Pediatric Surgery Reports, 2025)
Pleuropericardial cysts are rare mediastinal tumors with variable, often severe, clinical presentations in children, occasionally requiring urgent intervention. We report the case of a previously healthy 14-year-old male who was admitted with signs of severe congestive heart failure and clinical evidence of cardiac tamponade. Transthoracic echocardiography and thoracic CT scan confirmed the presence of a compressive mediastinal cystic mass. The patient underwent emergency surgical resection via median sternotomy. Histopathological examination confirmed a benign pericardial cyst. Postoperative recovery was uneventful, and no recurrence was observed after 2 years of follow-up.
Keywords: pleuropericardial cyst; child; surgical resection; sub-Saharan Africa